The efficacy of acupuncture for generalized anxiety disorder (GAD) in college students: Study protocol for a randomized controlled trial. - Yang Wang; Xinbo Gu; Baohua Zhi; Yan Yan; Fengyan Lu; Hantong Hu; Quanai Zhang (PLoS ONE)
Introduction Generalized anxiety disorder (GAD) is the most common type of anxiety disorders. GAD usually occurs in adolescence or early adulthood, and the prevalence of GAD is higher among college-enrolled young adults than in the general adult population. However, there is a lack of evidence regarding the effectiveness of acupuncture in the treatment of GAD. This study's objective is to evaluate the efficacy of acupuncture in the treatment of GAD in college students and its stability. Methods A total of 142 subjects will be recruited for the randomized controlled trial (RCT) of current undergraduate and graduate students with GAD and will be randomized into treatment and control groups. The treatment group will receive conventional acupuncture, while the control group will receive sham acupuncture using Streitberger needles. Both groups will be administered 8 acupuncture treatment (2 times per week for 4 weeks). The follow-up duration will be 2 months. The Hamilton Anxiety Scale (HAMA) will be used as the primary outcome of the study to measure the severity of anxiety disorder. The secondary outcomes of this study will be included the Pittsburgh Sleep Quality Index (PSQI) and Self-rating anxiety Scale (SAS). The study will also evaluate the success of blinding and the safety. Discussions Findings of this RCT will help evaluate the efficacy of acupuncture treatment for GAD in college students, potentially promoting it as an alternative treatment option. The protocol was registered at clinicaltrials.gov (Identifier: ChiCTR2400080688).